MAKNA TANDA VISUAL PADA SAMPUL BUKU TERJEMAHAN CERITA ANAK LEVEL 2 TERBITAN BADAN BAHASA: KAJIAN SEMIOTIKA PEIRCE - Habiba Tsalisa Shofiah; Adelia Savitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Children’s storybook covers play an important role in attracting reading interest while also conveying messages to child readers. This study aims to reveal the patterns and characterization of Badan Bahasa in creating illustrations for translated children’s book covers through the semiotic analysis of Charles Sanders Peirce. The method used is a descriptive qualitative method with Peirce’s semiotic approach, which analyzes signs based on the categories of icon, index, and symbol. The research data consist of eight covers of level 2 translated children’s books published by Badan Bahasa in 2021, which were analyzed based on illustrations, colors, character expressions, and other visual elements. The results show that the cover illustrations of Badan Bahasa publications have a visual pattern that is communicative and imaginative through the use of icons, indexes, and symbols that can represent the story content as well as support the delivery of messages and character values to child readers.